2007
DOI: 10.1007/s00396-007-1805-7
|View full text |Cite
|
Sign up to set email alerts
|

Size-controlled synthesis of monodisperse core/shell nanogels

Abstract: Small, monodispersed nanogels (~ 50-nm radius) were synthesized by free-radical precipitation polymerization and characterized using a suite of light scattering and chromatography methods. Nanogels were synthesized with either N-isopropylacrylamide or N-isopropylmethacrylamide as the main monomer, with acrylic acid or 4-acrylamidofluorescein as a co-monomer and N, N′-methylenebis(acrylamide) as a cross-linker. By varying the surfactant and initiator concentrations, particle size was controlled while maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 42 publications
3
101
1
Order By: Relevance
“…Flexible NIPAm particles of ~1100nm and ~850nm diameter passed through pores of 100nm diameter at levels commensurate with those observed for 88nm polystyrene beads [89,90] (Figure 2b). Alternative nanogels of 116nm diameter also passed through 10nm pores where 88nm polystyrene beads did not [89,91]. Earlier work indicated that nanogels with minimal cross-linking can experience a 15fold reduction in volume under compression [90].…”
Section: Modulation Of Vascular Targeting By Carrier Mechanical Prmentioning
confidence: 99%
“…Flexible NIPAm particles of ~1100nm and ~850nm diameter passed through pores of 100nm diameter at levels commensurate with those observed for 88nm polystyrene beads [89,90] (Figure 2b). Alternative nanogels of 116nm diameter also passed through 10nm pores where 88nm polystyrene beads did not [89,91]. Earlier work indicated that nanogels with minimal cross-linking can experience a 15fold reduction in volume under compression [90].…”
Section: Modulation Of Vascular Targeting By Carrier Mechanical Prmentioning
confidence: 99%
“…In applications such as a support for proteins and oligonucleotides that will be probed by fluorescence, the latexes need to be transparent in the region of absorption of protein intrinsic fluorophores, and the particle sizes should be within 200 nm or so [34]. In addition, the application of intravenous drug delivery such as targeted chemotherapy must be around 100 nm in diameter to be efficient vehicles so that particles can penetrate into discontinuous tumor vasculature [35]. Therefore, it is valuable to find a way to prepare the pH-and temperatureresponsive microgels at nanoscale in the absence of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the application, this collapse can trigger rapid burst release of the loaded drug or can result in decreased porosity and a more controlled drug release profile (35)(36)(37). Additionally, poly(NIPAm) is readily copolymerized with acrylic acid (AAc), which adds easily modified carboxylic acid functional groups to the backbone of the particle, allowing for the addition of targeting ligands while simultaneously increasing the colloidal stability of the nanoparticle (38)(39)(40)(41)(42). In addition to carboxylic acid, the charged sulfated comonomer 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS) has been added to poly(NIPAm) nanoparticles, resulting in colloidally stable, hemocompatible sulfated poly(NIPAm-AMPS) nanoparticles (29,43,44).…”
Section: Introductionmentioning
confidence: 99%